NEO SUFISME (SEJARAH DAN PROSPEKNYA) - Hermansyah Hermansyah (The Pontianak State Institute of Islamic Studies, 2013)
Once the tendency of mysticism was characterized by isolated spiritualism which separated its followers from the society. No wonder, many ulemas rejected this kind of Sufism. In the turbulence of modern human life, Sufism has become an alternative to consider since modernism (viewed fromcertain aspects) has failed to créate a more meaningful life for humans. However, nota ll the tendencies in the movement of Islamic spirituals can instantly overcome the meaninglessness of a society. The writed argues that the kind of Sufism that can answer this challenge is the one that is concerned with the problems of invironment, social ethics, and the future of humanity, which relies on the power of emperical knowledge and spiritual awareness that is mystical in nature. This kind of Sufism is what Fazlur Rahman referred to as neo-Sufism.